Taping with active exercises versus active exercise alone in management of shoulder impingement syndrome subjects - Bhat, Ishfaq Bashir (Acta Scientific, 2019)
Background of study: Shoulder problems are common complaint of the musculoskeletal system. Of all the shoulder problems shoulder impingement syndrome is one of the common. Treatment of shoulder impingement symptoms commonly includes exercises at first instance. Taping has been seen as an alternative treatment in SIS. Methods: A total of thirty patients were diagnosed with shoulder impingement syndrome. Among which 27 (F=11(40.7%) M=16(59.3%)) stayed were assigned to one of two treatment groups. 15 subjects in group A were treated with exercises along with some conventional pain modality (US or IFT). Subjects in group B (12) were treated with exercises along with taping. Taping was done once a week. Results: Within group comparison was done using paired t-test and between groups comparison was done using independent t- test with p – values matched at less than 0.001. There was significant improvement in SDQ and VAS in both groups. In group A SDQ improved from 59.53 ± 13.87 to 18.87 ± 15.32 and VAS decreased from 6.27 ± 1.44 to 2.00 ± 1.56. And in group B SDQ improved from 62.70 ± 19.47 to 23.05 ± 19.33 and VAS score decreased from 6.75 ± 1.71 to 1.92 ± 1.62. There was some improvement in ROM scores of shoulder flexion abduction and scaption in both groups but that was not significant. Conclusion: In conclusion there is promising evidence for efficacy of exercise treatment along with taping and other pain modalities in treatment of shoulder impingement syndrome. And it should be the choice of treatment in pry health care. However when comparing exercise along taping with exercises along with other pain modality. There is no such difference that one treatment option is better than second.